2004
DOI: 10.1177/10983007040060010201
|View full text |Cite
|
Sign up to set email alerts
|

The School-Wide Evaluation Tool (SET)

Abstract: Schools throughout the country are now encouraged to implement school-wide positive behavior support (PBS) procedures as a way to improve their behavioral climate, safety, and social culture. Research is needed to determine (a) the extent to which schools already use school-wide PBS, (b) if training and technical assistance efforts result in change in the use of school-wide PBS procedures, and (c) if use of these procedures is related to valued change in safety, social culture, and behavior within schools. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(94 citation statements)
references
References 21 publications
0
90
0
4
Order By: Relevance
“…During the assessment, the external observer assessed the degree to which a school has each of the model's seven critical features in place by reviewing written materials and established discipline procedures (e.g., discipline handbook, school improvement goals, behavioral incident summaries); noting visual displays of expected behaviors posted in various locations throughout the school; and interviewing administrators, teachers, and students about school procedures, policies, standards, and consequences for positive behavior and rule infractions. The SET has strong psychometric properties, including high internal consistency (Cronbach's alpha = .96), high inter-observer reliability, and strong test-retest reliability (Horner et al 2004). The developers of PBIS posited that the intended benefits of the program occur when the overall summary score on the SET (average score for all seven key features) reaches 80% (Horner et al 2004).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…During the assessment, the external observer assessed the degree to which a school has each of the model's seven critical features in place by reviewing written materials and established discipline procedures (e.g., discipline handbook, school improvement goals, behavioral incident summaries); noting visual displays of expected behaviors posted in various locations throughout the school; and interviewing administrators, teachers, and students about school procedures, policies, standards, and consequences for positive behavior and rule infractions. The SET has strong psychometric properties, including high internal consistency (Cronbach's alpha = .96), high inter-observer reliability, and strong test-retest reliability (Horner et al 2004). The developers of PBIS posited that the intended benefits of the program occur when the overall summary score on the SET (average score for all seven key features) reaches 80% (Horner et al 2004).…”
Section: Methodsmentioning
confidence: 98%
“…Yet the issue of program fidelity is of particular relevance for non-curricular and non-manualized school-based programs like PBIS, which are intended to be adaptable in different school contexts to address varying cultures, climates, and work attitudes . Consequently, the developers of PBIS created a multicomponent implementation quality measure called the School-wide Evaluation Tool (SET; Horner et al 2004), which can be used to monitor program fidelity over multiple years of implementation.…”
mentioning
confidence: 99%
“…Each implementation rating is criterionreferenced with regard to the specific practice in question. For a more in-depth description of the SET, please see Horner, Todd, Lewis-Palmer, Irvin, Sugai, and Boland (2004).…”
Section: Implementation Measuresmentioning
confidence: 99%
“…The elementary school had been implementing school-wide behavior support efforts for over four years. The School-Wide Evaluation Tool (SET; Horner et al, 2004) was administered during the spring of the school year prior to the current study and results indicated that, on average, the school was implementing their school-wide behavior support plan (Tier 1) with 88% fidelity. Data for all participants were collected in their general education classrooms during activities identified as most problematic during the functional behavioral assessment interviews (see below).…”
Section: Setting and Participantsmentioning
confidence: 99%